Immunosensor for bovine anaplasmosis diagnosis on graphite platform functionalized with poly (3-hydroxybenzoic acid) - Ferreira, Deusmaque Carneiro; Abrahão Júnior, Odonírio; Oliveira Júnior, Robson Tadeu Soares de; Souza Santos, Paula de; Brito Madurro, Ana Graci; Madurro, João Marcos (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
This study describes the development of an electrochemical immunosensor with a transducer platform functionalized with the poly-(3- hydroxybenzoic acid), to detection of antibodies against the surface protein (Am1) of Anaplasma marginale . This biological probe was immobilized on the polymer under graphite and characterized electrochemically. The detections of antigen-antibody interactions were conducted using the signal obtained from the oxidation of 4-aminoantipyrine (4 -AAP), interleaved with Am1, to enable the use of voltammetry technique of differential pulse. The detections of antibodies of A. marginable, using the graphite electrode functionalized with the probe Am1 was 66% higher than the graphite electrode not functionalized. The antigen (Am1) interacted with positive serum in dilutions of 1:1000, 1:800, 1:400, 1:200, 1:100, 1:50, and 1:25, demonstrating excellent sensitivity of the immunosensor. The time of storage of the immunosensor was satisfactory, with reduced peak current by 35%, after 90 days. The results demonstrate the excellent applicability of this new functionalized platform for probe immobilization and diagnosis of anaplasmosis without the interference of the most similar bovine diseases.